CODE-MIXING IN WRITING OPINION COLUM: CONTENT ANALYSIS AT MEDIA INDONESIA NEWSPAPER - La Ode Firima (Journal of Indonesian Language Education and Literary, 2018)
In daily conversation or comuniction and social interaction process appear a speaker to use language variation, like: code switching and code-mixing. This research only foced in code-mixing. Code-mixing was mixing foreign language elements in to the structure of main language. The purpose of this research was to describe the shape, background and function of the use of code-mixing in the opinion writing of Media Indonesia newspaper. This study used qualitative research. Based on the data analysis, obtainsed descriptions of the use of code-mixing form of phrases, words, baster and clauses, description of the background of code-mixing that used outer code-mixing and a description of the use of code-mixing which serves to identify the role, identification of diversity, and the desire to explain and interpret.